New Face of Contemporary Sufism in Southeast Asia: Experience of Indonesia and Malaysia - Muzakkir Syahrul; Ziaulhaq Hidayat (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2021)
The current global spiritual revival has been reflected in the revival of Sufism, to the extent that Sufism now has a different appearance from its earlier conventional manifestations. Global developments have driven Sufism to put its appearance relevant to the demands of global living. Focusing on the experiences of Indonesia and Malaysia, this paper attempts to examine the developments of Sufism. These countries seem to represent contemporary trends of Sufism in Southeast Asia. The new face of contemporary Sufism called “urban Sufism” is found in Indonesia. The practices of urban Sufism, which is influenced by the political realm, can be observed within Majelis Dzikir Nurussalam (MDN) established by the former President Susilo Bambang Yudhoyono. In Malaysia, the new appearance of Sufism was initiated by Dar al-Arqam, which later changed its name as Ikhwan Global (IG). This group actively encourages its members to be economically self-reliant by undertaking a range of business activities and at the same time promotes a Sufi lifestyle as the focus of its activities. This research found that contemporary Sufism is no longer oriented exclusively toward the pursuit of spiritual achievements, but it also becomes an instrument of political and economic interests.